(untitled) (Journal of Misan Researches, 2024)
This research aims to identify the internal interpretive tools adopted by Sheikh Abd al-Rahman al-Maidani (d. 1425 AH) in interpreting the steps of contemplation and the subtleties of contemplation, as he relied on a group of tools emanating from the text such as (language, morphology, derivation, and grammar). The research plan required that It is divided into an introduction and three sections. The introduction deals with the concept of interpretation, the life of the interpreter and his works, and the definition of interpretation. The first section dealt with the mechanism of (language) to determine the extent to which the interpreter depends on it, and what its impact is on the interpretive pluralism in interpreting the Book of God Almighty.